Women, Work and Welfare in the Middle East and North Africa 2016
DOI: 10.1142/9781783267347_0005
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Resources across the Life Course, and Cognitive Functioning in Egypt

Abstract: referential investments in the human resources of boys have been common to many resource-poor settings (King and Mason 2001;Lloyd 2005), and the effects of such investments on gender gaps in child health are known (e.g., Hill and Upchurch 1995). Less well known is the extent to which gender gaps in resources that are accrued across the life course account for gender gaps in later-life health, despite known gender differences in the risks of illness, disability, and death. Demographic research on later-life hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
3
12
0
Order By: Relevance
“…For future research, we should pay close attention to the current old cohort of men and women, who have not developed cognitive impairment, but will face their oldest-old age in the near future, because according to life-course perspectives, later cohorts that potentially possess higher cognitive functions will replace older cohorts with poor cognitive performance. 17,26 We need to follow this old cohort to see if they develop cognitive impairment as high as the current oldest-old cohort, especially women, as the majority of old women still did not have access to formal education. For that reason, we might need to follow current middle-aged men and women in China who have had the full advantages of formal education, as well as employment opportunities, to explore if their life environments would make any differences in the onset of cognitive impairment as they age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For future research, we should pay close attention to the current old cohort of men and women, who have not developed cognitive impairment, but will face their oldest-old age in the near future, because according to life-course perspectives, later cohorts that potentially possess higher cognitive functions will replace older cohorts with poor cognitive performance. 17,26 We need to follow this old cohort to see if they develop cognitive impairment as high as the current oldest-old cohort, especially women, as the majority of old women still did not have access to formal education. For that reason, we might need to follow current middle-aged men and women in China who have had the full advantages of formal education, as well as employment opportunities, to explore if their life environments would make any differences in the onset of cognitive impairment as they age.…”
Section: Discussionmentioning
confidence: 99%
“…Investment in women's educational attainment, spending an active lifestyle in a stimulating environment and involvement in cognitively challenging activities might help alleviate gender disparities. For future research, we should pay close attention to the current old cohort of men and women, who have not developed cognitive impairment, but will face their oldest‐old age in the near future, because according to life‐course perspectives, later cohorts that potentially possess higher cognitive functions will replace older cohorts with poor cognitive performance . We need to follow this old cohort to see if they develop cognitive impairment as high as the current oldest‐old cohort, especially women, as the majority of old women still did not have access to formal education.…”
Section: Discussionmentioning
confidence: 99%
“…33 As well, in countries marked by sex differences in education, increasing access and quality of education has the potential to improve women's cognitive health, in line with previous studies showing that women have a higher risk of CI and dementia than men. 34,35 For instance, Yount 36 found that 83% of the sex gap in mean MMSE scores could be attributable to sex differences in attributes across the life course, mainly education. Based on the baseline of SABE studies, Maurer 12 found that more than half of the overall difference in latelife cognition was a result of sex differences in educational attainment.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies found that retrospective reports of better global childhood health were associated with improved cognitive functioning in old age (Luo and Waite, 2005;Yi et al, 2007). Three others studies reported a null association (Barnes et al, 2012;Yount, 2016;Zhang et al, 2018). A single study examined the association between childhood infectious diseases and late-life cognitive functioning and showed mixed disease effects (Case and Paxson, 2009).…”
Section: Introductionmentioning
confidence: 99%